AB1050 Rentability of second percutaneous disco-vertebral biopsy (PDVB) in case of infectious spondylodiscitis (ISD). (23rd January 2014) - Carcasses, A.; Elsendoorn, A.; Brault, R.; Roblot, F.; Debiais, F.
Abstract : Background: When ISD is suspected, a second PDVB can be realised if the first analysis is negative. The rentability of this medical procedure remains insufficiently studied. Objectives: The study's objective was to evaluate the benefit of a second PDVB. Methods: This retrospective study included all patients hospitalised for ISD between 2005 and 2011 in the department of Rheumatology and Department of Infectious Diseases and Immunity for whom blood cultures and the first PDVB was negatives and who have had a second PDVB. For each patient we analysed clinical characteristics et microbiologics results. Results: One hundred and twenty four ISD were diagnosed during this period. The blood culture and the first PDVB remained negatives for 22 patients (18%). Among them, 6 had only one sample positive with commensal germ considerate as non pathogenic. Fourteen patients (11 men, 3 women, medium age 58 years (±13)) have had a second PDVB. The intervertebral localisation of ISD was lumbar (11 cases), cervical (2 cases) or thoracic (1 case). It was post operative ISD in 11 cases (79%). Results of second PDVB are: negatives in 8 cases, identification of microorganism considered as non pathogenic in 2 cases ( propionibacterium acnes and ruminococcus productus ); identification of the same microorganism as the one found in the first PDVB in 3 cases ( staphylococcus epidermidis, Propionibacterium acnes et Staphylococcus caprae ); identification of Staphylococcus saccharolyticus in 2 differents samples in 1 case. Conclusions: The second PDVB was contributive for the microbiologic diagnosis in 4 cases of 14 (29%). Bacteria revealed by the second PDVB were all commensal bacteria responsive to probabilist antibiotherapy such as recommanded by consensus conference. Disclosure of Interest: None Declared.